Evaluate the entrepreneurial trend in the success of small and medium enterprises (Jordan and Malaysia experience as a model) (Entrepreneurship Journal for Finance and Business, 2020)
This research aims to demonstrate the importance of entrepreneurship in the Hashemite Kingdom of Jordan and the State of Malaysia, as interest in entrepreneurship has increased at the present time, due to technological progress and the competitive environment of local, international and global projects that had a great impact on the business environment. Entrepreneurship is important in the growth of the economy The country at the macro level and on the growth and expansion of projects and their access to material and financial resources, in order to gain customer satisfaction, increase profitability and market share, and small and medium enterprises can only thrive in a society in which there is an entrepreneurial spirit, love of free work, willingness to take risks, adopt new ideas and understand the mechanisms of competition In the global market. The research problem arises in showing the level of entrepreneurship in Jordan and Malaysia, and this will be done through three sections, the first one includes the theoretical side of the research, and the second topic includes an analysis of the experiences of the Hashemite Kingdom of Jordan and Malaysia, and the third topic includes an analysis of Jordan’s data on entrepreneurship